Behavioral domains in compulsive rats: implications for understanding compulsive spectrum disorders - Martín-González, Elena; Olmedo-Córdoba, Manuela; Prados-Pardo, Ángeles; Cruz-Garzón, Daniel J.; Flores, Pilar; Mora, Santiago; Moreno-Montoya, Margarita (Frontiers in Behavioral Neuroscience, 2023)
Compulsive behavior has been proposed as a transdiagnostic trait observed in different neuropsychiatric disorders such as obsessive-compulsive disorder, autism, and schizophrenia. Research Domain Criteria (RDoC) strategy could help to disentangle the neuropsychological basis of compulsivity for developing new therapeutic and preventive approaches. In preclinical research, the selection of high drinker (HD) versus low drinker (LD) animals by Schedule-Induced Polydipsia (SIP) is considered a putative model of compulsivity, which includes a well differentiated behavioral pattern. The purpose of the present research was to assess the cognitive control and the negative valence system domains in a phenotype of compulsive HD rats. After the selection of animals as HD or LD, we assessed behavioral inflexibility by Probabilistic Spatial Reversal Learning (PSRL), motor and cognitive impulsivity by Variable Delay-to-Signal (VDS), and risky decision-making by Rodent Gambling Task (rGT). HD rats performed fewer reversals and showed less probability of pressing the same lever that was previously reinforced on PSRL, more premature responses after the exposure to longer delays on VDS, and more disadvantageous risky choices on rGT. Moreover, HD animals performed more perseverative responses under punishment period on rGT. These results highlight that HD compulsive phenotype exhibits behavioral inflexibility, insensitivity to positive feedback, waiting impulsivity, risky decision-making, and frustrative nonreward responsiveness. Moreover, these findings demonstrate the importance of mapping different behavioral domains to prevent, treat and diagnose compulsive spectrum disorders correctly.